Managing Projects in Large Companies – Project Success Factors in the Crisis and Post Crisis Period: Evidence from Serbia and Slovenia - Bjelica, Dragan; Mihić, Marko; Gošnik, Dušan (International Journal of Industrial Engineering and Management, 2026)
This paper investigates project success factors (SF) and project success criteria (SC) in large firms and aims to identify which contribute the most to project success. The results of this study are based on a survey of large firms in Slovenia and Serbia. A sample of 175 large firms is included. The Mann-Whitney test was used to compare groups across countries and between the COVID-19 and post COVID-19 periods. A comparison study of project SF and SC between the period of COVID-19 crisis and post COVID-19 is presented. Findings suggest a high degree of alignment between both countries: both prioritise user appreciation as the most important project SC and clear goals and objectives were identified as the most critical project SF. The results also show that a well-defined project management process is the most critical factor for successful project implementation. Project managers were constantly the most dominant decision makers on projects during and after the COVID-19 period. Analysis shows no significant differences between project SF and SF during and after the COVID-19 period, indicating that large companies are resilient in managing project success. Article history: Received (May 5, 2025); Revised (September 11, 2025); Accepted (December 8, 2025); Published online (February 12, 2026)